(untitled) (Istituto Lombardo - Accademia di Scienze e Lettere - Rendiconti di Scienze, 2014)
Properties of superhydrophobic materials are examined in light of their possible use for drag reduction in naval applications. To achieve superhydrophobicity a low-surface-energy material must be structured so as to minimize the liquid-solid interactions. The crucial aspect is that of maintaining a layer of gas in between the (rough) wall and the liquid, and this can be achieved by hierarchical micro- and nano-structuring of the solid surface, to ensure a sufficiently large apparent slip of the fluid at the wall, thus reducing skin friction. The behavior of the liquid is quantified by a slip length; recent results have shown that this length can be as large as 400 µm. As far as transition to turbulence is concerned, we show that superhydrophobic surfaces are effective (i.e. they delay the onset of travelling instability waves) only in channels with characteristic dimensions of a few millimeters. Conversely, when the fluid flow has already attained a turbulent state, the gain in term of drag reduction can be very significant also in macroscopic configurations. This occurs because the relevant length scale of the boundary layer is now the thickness of the viscous sub-layer, which can be of magnitude comparable to the slip length, so that an effective coupling emerges. Finally, some procedures to produce superhydrophobic surfaces are examined, in light of the possible application of such innovative coatings on the hull of ships.